N-acetyl-L-cysteine protects against cadmium-induced neuronal apoptosis by inhibiting ROS-dependent activation of Akt/mTOR pathway in mouse brain - Chen, Sujuan (2014)
AIMS: This study explores the neuroprotective effects and mechanisms of N-acetyl-L-cysteine (NAC) in mice exposed to cadmium (Cd). METHODS: NAC (150 mg/kg) was intraperitoneally administered to mice exposed to Cd (10-50 mg/L) in drinking water for 6 weeks. The changes of cell damage and death, reactive oxygen species (ROS), antioxidant enzymes, as well as Akt/mammalian target of rapamycin (mTOR) signaling pathway in brain neurons were assessed. To verify the role of mTOR activation in Cd-induced neurotoxicity, mice also received a subacute regimen of intraperitoneally administered Cd (1 mg/kg) with/without rapamycin (7.5 mg/kg) for 11 days. RESULTS: Chronic exposure of mice to Cd induced brain damage or neuronal cell death, due to ROS induction. Co-administration of NAC significantly reduced Cd levels in the plasma and brain of the animals. NAC prevented Cd-induced ROS and significantly attenuated Cd-induced brain damage or neuronal cell death. The protective effect of NAC was mediated, at least partially, by elevating the activities of Cu/Zn-superoxide dismutase, catalase and glutathione peroxidase, as well as the level of glutathione in the brain. Furthermore, Cd-induced activation of Akt/mTOR pathway in the brain was also inhibited by NAC. Rapamycin in vitro and in vivo protected against Cd-induced neurotoxicity. CONCLUSIONS: NAC protects against Cd-induced neuronal apoptosis in mouse brain partially by inhibiting ROS-dependent activation of Akt/mTOR pathway. The findings highlight that NAC may be exploited for prevention and treatment of Cd-induced neurodegenerative diseases.